2022
DOI: 10.3390/chemistry4010007
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Nitroarenes by Oxidation of Aryl Amines

Abstract: Nitro compounds are an important class of organic molecules with broad application in organic synthesis, medicinal chemistry, and materials science. Among the variety of methodologies available for their synthesis, the direct oxidation of primary amines represents an attractive alternative route. Efforts towards the development of oxidative procedures for the synthesis of nitro derivatives have spanned over the past decades, leading to a wide variety of protocols for the selective oxidative conversion of amine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…We found that our reaction tolerated a diverse array of substituents on the pyrimidine ring including several functional groups that are prone to reduction, such as exogenous halogen atoms [31] (compounds 3 , 4 , 5 ) and a nitrile [32] (compound 8 ). Unprotected aryl amines (prone to oxidation) [33] were also tolerated (compounds 7 and 8) . For a tosyl protected alcohol, our reaction conditions not only afforded the desired c NP product 9 , but also removed the tosyl protecting group in the same reaction.…”
Section: Resultsmentioning
confidence: 99%
“…We found that our reaction tolerated a diverse array of substituents on the pyrimidine ring including several functional groups that are prone to reduction, such as exogenous halogen atoms [31] (compounds 3 , 4 , 5 ) and a nitrile [32] (compound 8 ). Unprotected aryl amines (prone to oxidation) [33] were also tolerated (compounds 7 and 8) . For a tosyl protected alcohol, our reaction conditions not only afforded the desired c NP product 9 , but also removed the tosyl protecting group in the same reaction.…”
Section: Resultsmentioning
confidence: 99%